Penerapan Model Discovery Learning Berbantuan Media Audiovisual Berbasis Pembelajaran Daring untuk Meningkatkan Hasil Belajar Siswa Kelas V SD 3 Cranggang Kabupaten Kudus - Siti Maghfiroh; Widya Kusumaningsih; Fransiska Suciana (Universitas Pendidikan Mandalika, 2021)
The purpose of this study was to describe the improvement in learning outcomes of grade 5 elementary school students on theme 8 by applying the Discovery learning model assisted by audiovisual media. The research method used is classroom action research which is carried out in 3 cycles. Each cycle is carried out in 4 (four) stages, namely the planning, implementation, observation, and reflection stages. The subjects of this study were fifth grade students of SD 3 Cranggang. Data collection techniques by means of interviews, observations, tests, and documentation. While the data analysis technique used is descriptive qualitative and quantitative analysis. The results of this study indicate that the application of discovery learning learning models with audiovisual media can improve the learning outcomes of fifth grade students at SD 3 Cranggang on the theme 8 Neighborhoods of Our Friends, where the results of this increase are proven in each research cycle.